La reescritura prismática del orfismo y sus dimensiones en la poesía de Carles Riba, Agustí Bartra y Josep Sebastià Pons - Marta López Vilar (Interlitteraria)
According to historian of religions Marcel Detienne in his book The Writing of Orpheus, this figure is the origin of writing. From this point, I will propose the origin of this article, which will develop how Orphism – in its mythical and religious dimensions – is articulated within the poetic thought of the Catalan poets Carles Riba (1893–1959) and Agustí Bartra (1908–1982), and of the Rosellonian poet Josep Sebastià Pons (1886–1962).